Paramagnetic Meissner Effect and Current Flow in YBCO Nanofiber Mats - Pessoa, Alexsander L. [UNESP]; Koblischka-Veneva, Anjela; Carvalho, Claudio L. [UNESP]; Zadorosny, Rafael [UNESP]; Koblischka, Michael R. (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Microstructural and magnetic characterizations of YBa2Cu3O7-δ nanowire fabric-like samples were performed. Fabric-like ceramic superconductors are nanoporous materials and can be applied, e.g., in magnetic shielding, since the porous morphology makes them extremely light-weight and effectively to be cooled. The samples were produced by the solution blow spinning (SBS) technique, starting from a sol-gel solution of the precursor materials in polyvinyl-alcohol. The morphology of the samples was characterized by scanning electron microscopy, transmission electron microscopy, and X-ray diffraction with the aim to analyze the possible current paths. The magnetic hysteresis loops revealed typical polycrystalline behavior, and field-cooling in various small applied fields shows the presence of the paramagnetic Meissner effect (PME), but in a distinctly different way as compared to melt-texured Bi2Sr2CaCu2O8+δ or Nb.
Keywords: microstructure; nanowires; paramagnetic Meissner effect; YBCO